Analysis of naturally-generated corrosion products due to chlorides in 20-year old reinforced concrete: An elastic modulus-mineralogy characterization. (15th May 2021) - Rossi, Emanuele; Zhang, Hongzhi; Garcia, Santiago J.; Bijleveld, Johan; Nijland, Timo G.; Çopuroğlu, Oğuzhan; Polder, Rob B.; Šavija, Branko
Highlights: Micro-structural and –mechanical characterization of corrosion products was conducted. Corrosion products were naturally formed in different concrete mixes due to chlorides. The morphological textures were analyzed through microscopic analysis. The matrix of corrosion products was mainly made of goethite with maghemite marblings. A value between 80−100 GPa is suggested as Elastic modulus of corrosion products. Abstract: The elastic modulus of corrosion product (Ecp ) has been reported with significant variations in the literature. This study aims to investigate the Ecp of naturally-generated chloride-induced corrosion products formed in different concrete mixes. Microstructural characterization was conducted through nano-indentation, electron microscopy and Raman spectroscopy. The corrosion products were mainly composed of a goethite matrix with portions of maghemite, independently of the concrete composition. Microscopic analysis suggest that layers of corrosion products grow at different times and under different physico-chemical conditions. Our measurements showed that Ecp varied between 80−100 GPa, which can be suggested for numerical models of corrosion induced cracking.